2010
DOI: 10.1103/physreve.81.051301
|View full text |Cite
|
Sign up to set email alerts
|

Shear-driven size segregation of granular materials: Modeling and experiment

Abstract: Granular materials segregate by size under shear, and the ability to quantitatively predict the time required to achieve complete segregation is a key test of our understanding of the segregation process. In this paper, we apply the Gray-Thornton model of segregation (developed for linear shear profiles) to a granular flow with an exponential profile, and evaluate its ability to describe the observed segregation dynamics. Our experiment is conducted in an annular Couette cell with a moving lower boundary. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 25 publications
1
77
2
Order By: Relevance
“…Golick and Daniels [72] and May et al [104] performed ring shear segregation experiments which showed that under a confining pressure both the velocity profile, u = u(z), and the segregation rate, q = q(z), could have a strong height dependence and exact solutions for this case have been constructed [104,105]. Another interesting feature of these experiments is that they measured the degree of segregation based on the rise and fall of the top plate, which was caused by the grains packing denser in a mixed state than in a pure phase.…”
Section: Segregation In Bidisperse Mixturesmentioning
confidence: 99%
“…Golick and Daniels [72] and May et al [104] performed ring shear segregation experiments which showed that under a confining pressure both the velocity profile, u = u(z), and the segregation rate, q = q(z), could have a strong height dependence and exact solutions for this case have been constructed [104,105]. Another interesting feature of these experiments is that they measured the degree of segregation based on the rise and fall of the top plate, which was caused by the grains packing denser in a mixed state than in a pure phase.…”
Section: Segregation In Bidisperse Mixturesmentioning
confidence: 99%
“…In the meantime, a broad theoretical framework for segregation-driven pattern formation in dense flows is emerging (Gray & Thornton 2005;Gray & Chugunov 2006;Thornton et al 2006;May et al 2010;Wiederseiner et al 2011;Marks et al 2011;Thornton et al 2012;Kowalski & McElwaine 2013). This framework incorporates advection due to mean flow, percolation-driven segregation, and diffusion due to random particle collisions, in a continuum transport equation for the volume concentration of species i:…”
Section: Introductionmentioning
confidence: 99%
“…Here, we summarize results that will appear in a pair of papers [6,7]. The experimental setup and protocol are described in detail in [2].…”
Section: Experiments With a Couette Cellmentioning
confidence: 99%
“…In [6,7], we considered equation (1) with exponential fiunction u(z) and S(z) = s|u (z)|. However, we restricted attention to solutions independent of x, mimicking conditions in a Couette cell, in which layers of large and small particles are sheared by rotating a lower confining plate.…”
Section: Introductionmentioning
confidence: 99%